Contemporaneous Severity of Symptoms and Functioning Reflected by Variations in Reporting Doctor‐Diagnosed Osteoarthritis. Issue 6 (30th May 2013) - Peeters, Geeske; Parkinson, Lynne; Badley, Elizabeth; Jones, Mark; Brown, Wendy J.; Dobson, Annette J.; Mishra, Gita D.
<x xml:space="preserve">Abstract</x> Objective Osteoarthritis (OA) is acknowledged as an enduring condition; however, in epidemiologic studies, half of the participants who report having OA at one time may report not having it at a subsequent time. The aim of this study was to examine whether variations in reporting doctor‐diagnosed OA reflected concurrent fluctuations in indicators of disease severity in middle‐aged women. Methods Data were from 7, 623 participants (ages 50–55 years in 2001) in the Australian Longitudinal Study on Women's Health. Based on self‐report of doctor‐diagnosed OA at surveys in 2001, 2004, 2007, and 2010, the participants were classified according to pattern of OA reporting (e.g., 0‐0‐0‐0 = "no" on all surveys, 0‐1‐0‐1 = "no‐yes‐no‐yes"). Indicators of disease severity included frequency of joint pain/stiffness, use of antiinflammatory medications, and physical functioning assessed with the Short Form 36. Bar graphs were used to show concurrent variations in OA and markers, and associations were examined using log‐linear models. Results In this sample, 46% reported having OA on at least one survey, with half of these cases reporting not having OA at a later survey. The odds of reporting joint pain/stiffness often (odds ratio [OR] 7.26, 95% confidence interval [95% CI] 7.06–7.47) and taking antiinflammatory drugs (OR 4.44, 95% CI 2.37–8.33) were higher and physical functioning scores were lower (OR 3.75, 95% CI 3.56–3.95) when participants reported having OA. Conclusion Variations in reporting OA coincided with episodic fluctuations in symptoms and functioning. Inconsistent reporting of OA could therefore reflect the presence of symptoms rather than reporting error and should be considered in longitudinal studies.